HUBUNGAN ANTARA KASIH SAYANG DAN PERHATIAN TERHADAP KEPERCAYAAN DIRI REMAJA YANG TINGGAL DI PANI ASUHAN PUTRI AL-KAZEM ACEH BESAR - Rusli Yusuf; Ruslan Ruslan; Ati Winarni (Universitas Negeri Malang, 2018)
The purpose of article writing to determine the significant relationship between affection and attention to the confidence of adolescents living in the Al-Kazem Aceh Besar Orphanage. This research uses correlation method with quantitative approach. Data collection techniques used ques- tionnaires. While the sampling technique using total sampling. The total sampling technique in the study was all female teenagers living at the Al-Kazem Aceh Besar Orphanage, which amounted to 34 people, especially young women aged 11-17 years. The results of study show (1) The correlation coefficient between affection and adolescent self-confidence showed a fairly strong correlation level, (2) the correlation coefficient between attention and confidence showed strong relation rate, and (3) coefficient The correlation between affection and attention with adolescent self-confidence shows a fairly strong.